Applying coffee processing waste as an organic material against growth and yield of caisim plant (Brassica chinensis var. parachinensis) - Pramesti, Fadli Setio; Firnia, Dewi; Putri, Widia Eka; Sodiq, Abdul Hasyim (Universitas Wiralodra, 2024)
The research aimed to examine the quality of coffee waste in solid and liquid material in promoting the growth and yield of caisim plants (Brassica chinensis var. parachinensis). This research was conducted from November until December 2023 in Sukabumi Roadway, RT. 002 RW. 001 Ciwedus Village, Cilegon District, Cilegon city, Banten. The experimental design used in this study was a Randomized Block Design (RBD) consisting of one factor, which is with eight treatment levels: without fertilizer application (control) (P0), 10 g of solid coffee processing waste compost (P1), 20 g of solid coffee processing waste compost (P2), 30 g of solid coffee processing waste compost (P3), 100 ml liquid coffee processing waste compost (P4), 150 ml liquid coffee processing waste compost (P5), 200 ml liquid coffee processing waste compost (P6), and 250 ml liquid coffee processing waste compost (P7). The results showed that treatment P5, gave the best results in terms of growth in plant height (26.30 cm), number of leaves (9.00 leaves), plant fresh weight (43.23 g), root wet weight (4.03 g), and root length (17.80 cm). For solid coffee ground treatment, the P3 treatment has a significant effect on plant height (25.30 cm), number of leaves (7.00 leaves), plant wet weight (22.60 g), and root length (17.03 cm). The findings of this research theoretically support the theory proposed by Putri et al. in 2017, indicating that the application of 30g/150 ml had the most favorable impact on the growth of lettuce plants (Lactuca sativa L.).